Potensi Atlet E-Sport Sebagai Olahraga Prestasi - Rohmad Apriyanto; Olivia Dwi Cahyani; Hasan Saifuddin; Heru Iswanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The e-sport branch is very likely to produce professional athletes. The interests and talents and potential of the community need to be given space and place to match the development of changes in social behavior in the community. Understanding e-sport as an achievement sport needs to be emphasized in order to form positive social values in society. Video games with certain types of genres are now competing in national and international championship competitions. The results of community service socialization of e-sport as an achievement sport for the level of understanding of the youth community in Klampok village are 91.7%, the remaining 8.3% of the community do not know e-sport as an achievement sport. the percentage of people who play video games according to the type of genre competed in the regional / national level e-sport championship event is 32.4%, the remaining 67.7% of the community play video games that are not competed in the regional / national level e-sport competition. People who have participated in good e-sport competitions at the regional / national level are at 20.3%, for gadget specifications that are used adequately in playing e-sport there are 58.3%, social environmental support factors 65.5%, parental support factors 8.3%.